Alumina modified graphene, graphene modified concrete and preparation method of alumina modified graphene and graphene modified concrete
By adding surfactant to alumina modified graphene and performing heating reactions, the problem of insufficient dispersion and stability in concrete is solved, and the stability and performance of concrete are significantly improved.
Patent Information
- Application Number
- CN202411770409.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-18
AI Technical Summary
Alumina modified graphene is insufficient in dispersion and stability in concrete, resulting in the impact of the uniformity and performance of concrete.
Surfactant is added to alumina modified graphene, and its dispersion and stability in concrete are improved by heating reaction.
The stability of concrete is significantly improved, water resistance and mechanical properties are maintained, and the compressive strength loss is low after freeze-thaw cycle.
Smart Images

Figure BDA0005170129110000071 
Figure BDA0005170129110000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and specifically relates to an alumina-modified graphene, a graphene-modified concrete and a preparation method thereof. Background Art
[0002] With the rapid development of the construction industry, the performance requirements for concrete materials are increasing. Traditional concrete materials have certain limitations in terms of water resistance, durability and mechanical properties, and it is difficult to meet the needs of modern engineering for high-performance concrete. Therefore, the development of new high-performance concrete materials has become a current research hotspot.
[0003] As a new type of two-dimensional nanomaterial, graphene has shown great application potential in the field of composite materials due to its unique structure and excellent physical and chemical properties. Especially in the field of concrete, the addition of graphene can effectively improve the mechanical properties, durability and impermeability of concrete. However, the dispersion and stability of graphene in concrete have always been the key factors restricting its application.
[0004] Alumina, as a common inorganic material, is also widely used in the modification of composite materials. Alumina-modified graphene can not only improve the dispersibility of graphene, but also further enhance the mechanical properties and thermal stability of composite materials. However, directly adding alumina-modified graphene to concrete still faces the problem of insufficient stability, which can easily lead to the agglomeration and sedimentation of graphene in concrete, thus affecting the uniformity and performance of concrete. Summary of the invention
[0005] The present invention significantly improves the dispersibility and stability of alumina-modified graphene in concrete by adding a surfactant to the alumina-modified graphene, thereby improving the stability of the concrete; at the same time, it does not affect the water impermeability and mechanical properties.
[0006] In order to achieve the above object, the present invention can adopt the following technical solutions:
[0007] On one hand, the present invention provides a method for preparing aluminum oxide modified graphene, comprising: mixing a graphene aluminum nitrate mixed solution and a surfactant, and heating the mixture to react to obtain the aluminum oxide modified graphene.
[0008] Preferably, the surfactant is selected from one or more of polydimethyldiallylammonium chloride, sodium dodecylbenzenesulfonate, a silane coupling agent or hexadecyltrimethylammonium bromide.
[0009] More preferably, the above surfactant is selected from polydimethyldiallylammonium chloride.
[0010] Preferably, the mass of the above-mentioned surfactant is 0.2%-0.7% of the mass of the graphene aluminum nitrate mixed solution.
[0011] More preferably, the mass of the polydimethyldiallylammonium chloride is 0.5% of the mass of the graphene aluminum nitrate mixed solution.
[0012] More preferably, the temperature of the heating reaction is 140°C-170°C.
[0013] Another aspect of the present invention provides an aluminum oxide modified graphene, which is prepared by the preparation method of the present invention.
[0014] In another aspect, the present invention provides a graphene-modified concrete, which comprises a base concrete and the alumina-modified graphene of the present invention.
[0015] Preferably, the mass of the alumina-modified graphene is 0.1%-0.5% of the base concrete.
[0016] More preferably, the mass of the alumina-modified graphene is 0.3% of the base concrete.
[0017] The beneficial effects of the present invention include: the modified concrete prepared based on the alumina-modified graphene provided by the present invention has excellent water resistance and mechanical properties, and also has excellent stability. For example, the compressive strength loss after 20 freeze-thaw cycles can be as low as 6.6%, and the compressive strength loss after 50 freeze-thaw cycles can be as low as 7.9%. DETAILED DESCRIPTION
[0018] The examples are provided to better illustrate the present invention, but the present invention is not limited to the examples. Therefore, those skilled in the art may make non-essential improvements and adjustments to the implementation scheme according to the above invention content, which still fall within the protection scope of the present invention.
[0019] The terms used herein are only used to describe specific embodiments and are not intended to limit the present disclosure. Unless the context has a significantly different meaning, expressions in the singular include expressions in the plural. As used herein, it should be understood that terms such as "include", "have", "include" are intended to indicate the presence of features, numbers, operations, components, parts, elements, materials or combinations. The terms of the present invention are disclosed in the specification, and are not intended to exclude the possibility that one or more other features, numbers, operations, components, parts, elements, materials or combinations thereof may exist or may be added. As used herein, " / " may be interpreted as "and" or "or", depending on the circumstances.
[0020] The embodiment of the present invention provides a method for preparing aluminum oxide modified graphene, comprising: mixing a graphene aluminum nitrate mixed solution and a surfactant, and heating the mixture to react to obtain the aluminum oxide modified graphene.
[0021] It should be noted that the present invention finds that by adding a surfactant to the existing alumina-modified graphene, the dispersion stability of the alumina-modified graphene in the concrete can be improved, thereby improving the stability of the concrete. In addition, the graphene aluminum nitrate mixed solution is well known in the art and can be obtained by a preparation method well known in the art.
[0022] In some specific examples, the surfactant is selected from one or more of polydimethyldiallylammonium chloride, sodium dodecylbenzenesulfonate, a silane coupling agent or hexadecyltrimethylammonium bromide.
[0023] It should be noted that the surfactant in the present invention may preferably be one or more of polydimethyldiallyl ammonium chloride, sodium dodecylbenzene sulfonate, a silane coupling agent or hexadecyltrimethylammonium bromide; among them, polydimethyldiallyl ammonium chloride (PDMDAAC) is more preferred, and the stability of polydimethyldiallyl ammonium chloride is better than that of sodium dodecylbenzene sulfonate, a silane coupling agent and hexadecyltrimethylammonium bromide.
[0024] In some specific examples, the mass of the surfactant is 0.2%-0.7% of the mass of the graphene aluminum nitrate mixed solution, such as 0.3%, 0.4%, 0.5% or 0.6%.
[0025] It should be noted that if the amount of surfactant added is too little, the dispersion effect cannot be achieved. If the amount of surfactant added is too much, the dispersion effect will also be affected. Among them, the added amount can be further preferably 0.5%. The modified graphene prepared at this ratio makes the concrete more stable.
[0026] In some specific examples, the temperature of the heating reaction is 140°C-170°C, such as 145°C, 150°C, 155°C, 160°C or 165°C.
[0027] It should be noted that the heating reaction of the present invention is consistent with the heating reaction of the existing method for preparing aluminum oxide-modified graphene, and the existing method for preparing aluminum oxide-modified graphene can be referred to.
[0028] An embodiment of the present invention further provides an aluminum oxide-modified graphene, which is prepared by the preparation method of the present invention.
[0029] An embodiment of the present invention further provides a graphene-modified concrete, which includes a base concrete and the alumina-modified graphene of the present invention.
[0030] It should be noted that, as described above, the alumina-modified graphene in the present invention can be applied to concrete modification, and the alumina-modified graphene in the present invention can be well dispersed in concrete, thereby improving the stability of concrete. For example, the loss of compressive strength of the modified concrete prepared by the present invention can be as low as 6.6% after 20 freeze-thaw cycles, and the loss of compressive strength after 50 freeze-thaw cycles can be as low as 7.9%.
[0031] In some specific examples, the mass of the above-mentioned alumina-modified graphene is 0.1%-0.5% of the base concrete, such as 0.2%, 0.3% or 0.4%, etc., among which 0.3% is more preferred. The modified concrete prepared at this ratio has better stability.
[0032] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific examples, but the content of the present invention is not limited to the following examples.
[0033] 1. Preparation of modified graphene
[0034] Example 1
[0035] (1) adding 4 g of graphene powder to 2000 g of aluminum nitrate solution (0.5 g / mL), centrifuging (5000 rpm) for 40 min to uniformly disperse the graphene in the aluminum nitrate solution to obtain a graphene aluminum nitrate mixed solution;
[0036] (2) filtering the graphene aluminum nitrate mixed solution to obtain a filtrate;
[0037] (3) adding 4 g of polydimethyldiallylammonium chloride to the filtrate and mixing well to obtain a mixed solution;
[0038] (4) The mixed solution is heated at 160° C. for 0.5 h to obtain alumina-modified graphene.
[0039] Example 2
[0040] (1) adding 4 g of graphene powder to 2000 g of aluminum nitrate solution (0.5 g / mL), centrifuging (5000 rpm) for 40 min to uniformly disperse the graphene in the aluminum nitrate solution to obtain a graphene aluminum nitrate mixed solution;
[0041] (2) filtering the graphene aluminum nitrate mixed solution to obtain a filtrate;
[0042] (3) adding 10 g of polydimethyldiallylammonium chloride to the filtrate and mixing well to obtain a mixed solution;
[0043] (4) The mixed solution is heated at 160° C. for 0.5 h to obtain alumina-modified graphene.
[0044] Example 3
[0045] (1) adding 4 g of graphene powder to 2000 g of aluminum nitrate solution (0.5 g / mL), centrifuging (5000 rpm) for 40 min to uniformly disperse the graphene in the aluminum nitrate solution to obtain a graphene aluminum nitrate mixed solution;
[0046] (2) filtering the graphene aluminum nitrate mixed solution to obtain a filtrate;
[0047] (3) adding 14 g of polydimethyldiallylammonium chloride to the filtrate and mixing well to obtain a mixed solution;
[0048] (4) The mixed solution is heated at 160° C. for 0.5 h to obtain alumina-modified graphene.
[0049] Example 4
[0050] (1) adding 4 g of graphene powder to 2000 g of aluminum nitrate solution (0.5 g / mL), centrifuging (5000 rpm) for 40 min to uniformly disperse the graphene in the aluminum nitrate solution to obtain a graphene aluminum nitrate mixed solution;
[0051] (2) filtering the graphene aluminum nitrate mixed solution to obtain a filtrate;
[0052] (3) adding 10 g of sodium dodecylbenzene sulfonate to the filtrate and mixing well to obtain a mixed solution;
[0053] (4) The mixed solution is heated at 160° C. for 0.5 h to obtain alumina-modified graphene.
[0054] Example 5
[0055] (1) adding 4 g of graphene powder to 2000 g of aluminum nitrate solution (0.5 g / mL), centrifuging (5000 rpm) for 40 min to uniformly disperse the graphene in the aluminum nitrate solution to obtain a graphene aluminum nitrate mixed solution;
[0056] (2) filtering the graphene aluminum nitrate mixed solution to obtain a filtrate;
[0057] (3) adding 10 g of silane coupling agent to the filtrate and mixing evenly to obtain a mixed solution;
[0058] (4) The mixed solution is heated at 160° C. for 0.5 h to obtain alumina-modified graphene.
[0059] Example 6
[0060] (1) adding 4 g of graphene powder to 2000 g of aluminum nitrate solution (0.5 g / mL), centrifuging (5000 rpm) for 40 min to uniformly disperse the graphene in the aluminum nitrate solution to obtain a graphene aluminum nitrate mixed solution;
[0061] (2) filtering the graphene aluminum nitrate mixed solution to obtain a filtrate;
[0062] (3) adding 10 g of hexadecyltrimethylammonium bromide to the filtrate and mixing well to obtain a mixed solution;
[0063] (4) The mixed solution is heated at 160° C. for 0.5 h to obtain alumina-modified graphene.
[0064] Comparative Example 1
[0065] (1) adding 4 g of graphene powder to 2000 g of aluminum nitrate solution (0.5 g / mL), centrifuging (5000 rpm) for 40 min to uniformly disperse the graphene in the aluminum nitrate solution to obtain a graphene aluminum nitrate mixed solution;
[0066] (2) filtering the graphene aluminum nitrate mixed solution to obtain a filtrate;
[0067] (3) The filtrate is heated at 160° C. for 0.5 h to obtain alumina-modified graphene.
[0068] 2. Modified concrete preparation
[0069] In the following examples, the base concrete used is 42.5R cement concrete from China Resources Cement.
[0070] Example 7
[0071] 7 g of alumina-modified graphene prepared in Example 2, 7 kg of base concrete and 3.5 kg of water were mixed, and stirred at 80 r / min for 3 min to obtain modified concrete.
[0072] Example 8
[0073] 21 g of the alumina-modified graphene prepared in Example 2, 7 kg of base concrete and 3.5 kg of water were mixed, and stirred at 80 r / min for 3 min to obtain modified concrete.
[0074] Example 9
[0075] 35 g of the alumina-modified graphene prepared in Example 2, 7 kg of base concrete and 3.5 kg of water were mixed, and stirred at 80 r / min for 3 min to obtain modified concrete.
[0076] Example 10
[0077] 21 g of the alumina-modified graphene prepared in Example 1, 7 kg of base concrete and 3.5 kg of water were mixed, and stirred at 80 r / min for 3 min to obtain modified concrete.
[0078] Embodiment 11
[0079] 21 g of the alumina-modified graphene prepared in Example 3, 7 kg of base concrete and 3.5 kg of water were mixed, and stirred at 80 r / min for 3 min to obtain modified concrete.
[0080] Example 12
[0081] 21 g of the alumina-modified graphene prepared in Example 4, 7 kg of base concrete and 3.5 kg of water were mixed, and stirred at 80 r / min for 3 min to obtain modified concrete.
[0082] Embodiment 13
[0083] 21 g of the alumina-modified graphene prepared in Example 5, 7 kg of base concrete and 3.5 kg of water were mixed, and stirred at 80 r / min for 3 min to obtain modified concrete.
[0084] Embodiment 14
[0085] 21 g of the alumina-modified graphene prepared in Example 6, 7 kg of base concrete and 3.5 kg of water were mixed, and stirred at 80 r / min for 3 min to obtain modified concrete.
[0086] Comparative Example 2
[0087] 21 g of the alumina-modified graphene prepared in Comparative Example 1, 7 kg of base concrete and 3.5 kg of water were mixed, and stirred at 80 r / min for 3 min to obtain a modified concrete.
[0088] 3. Verification of modified concrete effect
[0089] In the following verification, the preparation method of the concrete reagent is carried out according to the following steps: pour the modified concrete into the prepared mold (150mm×150mm×150mm), use a vibration table to compact the concrete, then use a trowel to smooth the surface of the test block, and cover the test block tightly with a wet sack; cure for 28 days in a standard curing room at a temperature of 20℃±2℃ and a humidity of more than 95% to obtain a concrete specimen.
[0090] (1) Changes in appearance
[0091] After 28 days of curing, the appearance of the concrete specimens prepared in Examples 7 to 14 and Comparative Example 2 were observed, as shown in Table 1 below.
[0092] Table 1 Appearance of different concrete specimens
[0093] Example / Comparative Example Appearance Example 7 No obvious cracks, no obvious deformation Example 8 No obvious cracks, no obvious deformation Example 9 No obvious cracks, no obvious deformation Example 10 No obvious cracks, no obvious deformation Embodiment 11 No obvious cracks, no obvious deformation Example 12 No obvious cracks, no obvious deformation Embodiment 13 No obvious cracks, no obvious deformation Embodiment 14 No obvious cracks, no obvious deformation Comparative Example 2 No obvious cracks, no obvious deformation
[0094] It can be seen from Table 1 above that the concrete specimens prepared in the embodiments and comparative examples have no obvious cracks and obvious deformations in appearance and meet the use requirements, indicating that adding ionic surfactants to the graphene alumina modifier has no obvious effect on the appearance of the concrete specimens compared to not adding them.
[0095] (2) Freeze-thaw cycle test
[0096] Then, the mechanical properties of the concrete were tested according to the method in GB / T50081-2002; referring to GB / T50082-2009, the standard for test methods for long-term performance and durability of ordinary concrete, the concrete specimens prepared in the above Examples 7 to 14 and Comparative Example 2 were tested respectively, and the test results are shown in Table 2.
[0097] Table 2 Compressive strength of different concrete specimens after freeze-thaw cycles
[0098]
[0099] The compressive strength loss of different concrete specimens after freeze-thaw cycles was calculated according to Table 2 above, and the results are shown in Table 3 below.
[0100] Table 3 Compressive strength loss ratio of different concrete specimens after freeze-thaw cycles
[0101]
[0102] It can be seen from Table 3 above that the compressive strength loss of the concrete specimens prepared in the embodiment after 20 freeze-thaw cycles is lower than that of the comparative example, among which the loss of Example 8 is the smallest; and after 50 freeze-thaw cycles, the compressive strength loss of the concrete specimens prepared in the embodiment is much lower than that of the comparative example, among which the loss of Example 8 is also the smallest.
[0103] In addition, by comparing Examples 7 to 14 and Comparative Example 2, it can be seen that adding polydimethyldiallylammonium chloride, sodium dodecylbenzenesulfonate, silane coupling agent and hexadecyltrimethylammonium bromide to the graphene alumina modifier can significantly reduce the loss compared to not adding them, which means that the addition of surfactants improves the stability of concrete.
[0104] In addition, by comparing Example 8 with Example 7 and Example 9 with Example 14, it can be seen that adding polydimethyldiallyl ammonium chloride to the graphene alumina modifier reduces the loss less than adding sodium dodecylbenzene sulfonate, silane coupling agent and hexadecyltrimethylammonium bromide, indicating that adding polydimethyldiallyl ammonium chloride is better than adding sodium dodecylbenzene sulfonate, silane coupling agent and hexadecyltrimethylammonium bromide.
[0105] (3) Water permeability test
[0106] After the concrete specimens prepared in Example 8 to Comparative Example 2 were dried to constant weight, the water permeability of the concrete specimens was tested respectively according to the constant head method in the standard GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", and the results are shown in Table 4 below.
[0107] Table 4 Water permeability of different concrete specimens
[0108] Example / Comparative Example Permeability coefficient Example 8 0.15cm / s Comparative Example 2 0.17cm / s
[0109] It can be seen from Table 4 above that there is no obvious difference in the permeability coefficient between Example 8 and Comparative Example 2, which shows that the addition of polydimethyldiallylammonium chloride to the graphene alumina modifier in the present invention will not affect the water resistance of concrete.
[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be covered by the scope of the claims of the present invention.
Claims
1. A method for preparing alumina-modified graphene, characterized in that: include: A graphene aluminum nitrate mixed solution is mixed with a surfactant and heated to react to obtain aluminum oxide modified graphene.
2. The preparation method according to claim 1, characterized in that: The surfactant is selected from one or more of polydimethyldiallylammonium chloride, sodium dodecylbenzenesulfonate, a silane coupling agent or hexadecyltrimethylammonium bromide.
3. The preparation method according to claim 2, characterized in that: The surfactant is selected from polydimethyldiallylammonium chloride.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The mass of the surfactant is 0.2%-0.7% of the mass of the graphene aluminum nitrate mixed solution.
5. The preparation method according to claim 4, characterized in that: The mass of polydimethyldiallylammonium chloride is 0.5% of the mass of the graphene aluminum nitrate mixed solution.
6. The preparation method according to claim 1, 2, 3 or 5, characterized in that: The temperature of the heating reaction is 140°C-170°C.
7. An aluminum oxide modified graphene, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 6.
8. Graphene modified concrete, characterized in that: It comprises base concrete and the alumina-modified graphene as claimed in claim 7.
9. The graphene-modified concrete according to claim 8, characterized in that: The mass of alumina-modified graphene is 0.1%-0.5% of the base concrete.
10. The graphene-modified concrete according to claim 9, characterized in that: The mass of alumina-modified graphene is 0.3% of the base concrete.